The size-fractionated composition of particulate biogenic silica and its ecological significance in the Changjiang Estuary area - Xizhen Liu; Xizhen Liu; Bin Wang; Bin Wang; Siyang Chen; Haiyan Jin; Haiyan Jin; Yanpei Zhuang; Zhibing Jiang; Hongliang Li; Hongliang Li; Jianfang Chen; et al. (Frontiers in Marine Science)
The concentrations and distributions of particulate biogenic silica (PBSi) and its size-fractionated composition (>20 μm, 0.8–20 μm) of the Changjiang Estuary and its adjacent area were investigated during the summer of 2011. PBSi, primarily produced by diatoms in the surface waters of oceans, was examined for correlations with hydrographic conditions, nutrients, particulate organic carbon, and dissolved oxygen. The distribution of PBSi showed distinct patterns: high levels in nearshore, but relatively low further offshore; low concentrations in the surface layer, whereas relatively high concentrations in the bottom layer. Large-sized PBSi (>20 μm) prevailed in the surface layer, whereas small-sized PBSi (0.8–20 μm) dominated in the bottom layer. Temperature and nutrients were crucial factors controlling the grain size structure and distribution of PBSi. Further, we observed that the distinct zones of high PBSi values in the surface waters were affected by the Changjiang freshwater flushing, and those in the bottom waters were affected by the Yellow Sea Cold Water masses. Moreover, in the area where >20-μm PBSi prevailed, the silicate-to-nitrate ratio was less than 1 at most sampling stations, rendering silicate the limiting nutrient in this area. The PBSi/particulate organic carbon values in the surface waters of the study area ranged from 0.01 to 0.3. Areas exhibiting values exceeding 0.13 primarily clustered in nearshore waters, which was characterized by a dominance of large-sized (>20 μm) PBSi. The nearshore benthic waters exhibited anoxic conditions, where diatoms predominantly comprised the phytoplankton biomass and organic matter featured marine phytoplankton. Consequently, the proliferation of diatoms (siliceous phytoplankton) in the midupper water significantly contributed to the hypoxic conditions at the bottom, as diatoms underwent dissolution during sedimentation, leading to oxygen depletion.